Factores socioeconómicos que influyeron en el nivel de emprendimiento en el departamento de Loreto, durante el periodo 2019 - Vásquez Villacorta, Carlos (2022)
Entrepreneurship plays a fundamental role for the development and growth of the economy, so our research aims to determine the influence of socioeconomic factors on the level of entrepreneurship in the department of Loreto, in the period 2019. developed quantitative, correlational and non-experimental design research. The study includes as a population 764,506 individuals who belong to the Working Age Population (PET) of Loreto in 2019; the analysis was developed using the values of the Logit model. In which we find that there is no relationship between the level of entrepreneurship and the Socioeconomic classification in the department of Loreto, during the 2019 period, since it is not significant because the value of P>| t | is greater than 0.05. On the other hand, the estimated marginal effects of the Age variable is dy/dx = 0.0005931, which indicates that, as the person increases one year of age, their probability of having a business increases around 0.059%.